FACTORS THAT EFFECT ENVIRONMENTAL AWARENESS AMONG RESIDENTS REGARDING THE DISPOSAL OF E-WASTE IN TAMAN DESA RASAH - Farah Adilla Ab Rahman; Muhammad Nur Fahmi Ahmad Fadzil; Muhd Munirul Hakimi Ishak; Jeniwaty Mohd Jody (Journal of Islamic, Social, Economics and Development, 2023)
E-waste, which refers to discarded electronic equipment, parts, and materials, poses a serious threat to environmental sustainability and energy conservation. Raising community awareness about sustainable e-waste management is essential to address this issue. This article aims to assess the level of ecological consciousness in the Taman Desa Rasah community toward e-waste management. Quantitative research methods and convenience sampling were employed, with 200 participants completing a questionnaire tool over the course of the study. Data were analyzed using SPSS software. The study revealed that while respondents had a high level of e-waste management knowledge, their attitudes and practices were only moderate. These findings can serve as a valuable reference for government, non-governmental organizations, authorities, and the community to establish a more sustainable and responsible approach to e-waste management in their community.